An Intellectual Review Of Ghulam Mustafa Qamar’s Natiya Poetry - Dr. Zahid Akhter Shaheen , Dr. Shazia Andalib , Nazim Hussain , Muhammad Sajid (Migration Letters, 2024)
The tradition of poetry in Urdu literature is very old. Naat means to describe the glory of the Lord of the Universe, the Holy Prophet (peace be upon him). First of all, God Almighty said Naat in honor of His Beloved. Naat refers to the praise and praise of the Holy Prophet (pbuh). Naat poetry does not require any specific format or tradition, but Naat can be written in any poetic form or method, for example Ghazal, Masnavi, Masad, Rabai and Ghurmah. Rahma Yar Khan is an ancient and fertile district. The people of this district have earned a goo[1]d name in various fields of life, whether it is the field of literature, education, journalism and literature, the creators here are second to none. Creators like Khawaja Ghulam Farid, Makhdoom Hameeduddin Hakim, Muhammad Yar Faridi, Farooq Al Qadri, Maulvi Sultan Ali, Qais Faridi, made the land of Rahim Yar Khan prominent in the field of Sufism not only at the national but also at the international level. Apart from this, another literary figure belonging to Rahim Yar Khan district is Ghulam Mustafa Qamar, who is a reliable name in Urdu Natia poetry. Ghulam Mustafa Qamar has made the biography of Prophet Muhammad (pbuh) as his subject. A well-known book of his Natiya poetry "Talart Siraj Munar" has been published. Which has a unique status among Natia poetry.